1975
DOI: 10.1111/j.1432-1033.1975.tb04033.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Instability of Myelin Proteins

Abstract: Myelin basic protein, purified from bovine spinal cord, is cleaved by a purified bovine brain acid proteinase to yield three peptide fragments which were purified by gel filtration procedures combined with preparative gel electrophoresis. The purity of the fragments was established by end group analysis, amino acid analysis, polyacrylamide disc gel electrophoresis, and by their encephalitogenic activity. Chemical and biological characterization shows that one'peptide, (peptide 11), originates from the N-termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Although C-terminal deamidating enzymes are known to occur and may be responsible for inactivating thyrotropin-releasing hormone [12], there is no evidence that substance P is inactivated by deamidation [19,30]. More recent studies on a thyroliberin-deamidating enzyme purified from rat [50] and bovine [22] brain have shown that this enzyme can also cleave other neuropeptidades such as luliberin, angiotensin I and neurotensin on the carboxyl side of their proline residues, and hence is referred to as a 'postproline cleaving enzyme'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although C-terminal deamidating enzymes are known to occur and may be responsible for inactivating thyrotropin-releasing hormone [12], there is no evidence that substance P is inactivated by deamidation [19,30]. More recent studies on a thyroliberin-deamidating enzyme purified from rat [50] and bovine [22] brain have shown that this enzyme can also cleave other neuropeptidades such as luliberin, angiotensin I and neurotensin on the carboxyl side of their proline residues, and hence is referred to as a 'postproline cleaving enzyme'.…”
Section: Discussionmentioning
confidence: 99%
“…These include both cytosolic [12-151 and membrane-bound [13,14,16-181 substance-Pdegrading enzyme activities. A cytosolic enzyme has been partially purified from rat brain and shown to release phenylalanine and leucine preferentially from substance P, suggesting cleavage at two or more internal peptide bonds (Gln6-Phe7 or Phe7-Phe' and Glyg-Leu") [19]. Akopyan and coworkers [20] purified a neutral endopeptidase from bovine hypothalamus which degraded luteinizing-hormone-releasing hormone (luliberin) and somatostatin and also cleaved substance P, probably between Gln6-Phe' and Phe7-Phe'.…”
mentioning
confidence: 99%
“…Among these enzymes, the pyroglutamate aminopeptidase [17,181, the postproline-cleaving enzyme [19 -211, a nonchymotrypsin-like endopeptidase [22, 231, a cation-sensitive neutral endopeptidase [24,251, two other endopeptidases [26,271 and several aminopeptidases are present in the cytosol [28] and are thus excluded from the inactivation of extracellular peptides. Some of them, however, may be involved in the degradation after internalization of the peptide.…”
Section: Discussionmentioning
confidence: 99%
“…General protein degradation and turnover Many (including ↓) [36] Activation and degradation of polypeptide hormones, FGF [37] chemokines, growth factors and their receptors Plasminogen [38] Prolactin [39,40] Endostatin [41] Osteocalcin [42] Thyroglobulin [43] Insulin [44] Glucagon [45] IL-1 [46] IGFBP [47] Androgen receptor [48] Parathyroid hormone [49] MIP-1 alpha [50] MIP-1 beta [50] SLC [50] Activation of enzymatic precursors Cathepsin B [51,52] Cathepsin L [51,53] Transglutaminase 1 [54] Brain antigen processing Amyloid beta A4 protein [55,56] Tau [57] Tubulin [58] Myelin basic protein [59] Mhtt [60] Apolipoprotein E [61] Alpha-synuclein [62] Degradation of cytoskeletal proteins Neurofilaments [63] Actin [64,65] Myosin [64,66] Tropomyosin [65] Monocyte-mediated fibrinolysis Fibrinogen [67,68] Fibrin [67,68] Regulation of apoptosis Bid [69] Thiredoxin-1 [70] Processing of enzyme activators and inhibitors Prosaposin …”
Section: Biological Function Target Protein Referencementioning
confidence: 99%